Employment discrimination based on prior criminal conviction - Tasić Anđelija; Obradović Goran (Zbornik Radova Pravnog Fakulteta u Nišu, 2023)
In the context of employment, a form of direct discrimination is frequently embodied in prototypical examples of job advertisement, such as "A female worker needed to work in a bakery" or "Send a CV including a photo". The competent institutions often reacted to such and similar advertisements, and the citizens' awareness has been raised to such an extent that they often get organized (as "testers") to gather evidence and establish whether such conduct constitutes a discriminatory act. In this regard, the authors examine why some personal characteristics that are sometimes required from candidates (age, gender, appearance, etc.) are considered advantageous and do not cause the candidates revolt. How it is possible that even state authorities can ask the candidate for confirmation that he/she has not been convicted or that no legal proceeding is underway against him/her? Is the certificate on no prior criminal record really crucial for the position of a nurse or a medical technician (orderly) in cases where a person has been convicted of a minor offence against road safety? Is an unconvicted cook better at making sushi than the one convicted of negligently causing a car accident? How does the state provide for the possibility of resocialization of convicted offenders if it requires this type of certificate for jobs in the public sector, without making any distinction between the specific type of committed offence and the length of the imposed sentence? Finally, what about the presumption of innocence, one of the basic postulates of criminal procedure? By analyzing the current legal provisions and the practice of independent bodies and international institutions on this matter, the authors aim to address these and other questions that have been raised both in theory and in practice.